Suburban birds [videorecording (DVD)] - Qiu, Sheng (Director); Qiu, Sheng (Director); Li, Chun, 1990-; Huang, Lu, 1983-; Gong, Zihan (Cinema Guild, 2020)
While a team of engineers investigate a series of craters that have opened up on the outskirts of the city, a story of a boy whose friends start disappearing one by one unfolds, revealing the connection between these strange events.